2013
DOI: 10.1093/chemse/bjt053
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Capacity of Bulbar Projection Neurons During Development: A Quantitative Neuronal Analysis With Functional Correlation

Abstract: Critical periods and degrees of regeneration in injured olfactory bulbar projection neurons (mitral cells) were examined in adult rats whose lateral olfactory tracts (LOTs) were transected at different postnatal (P) days. After the LOTs were transected at P7, P10, and P14, a retrograde fluorescent tracer, Fluoro-Gold (FG), was injected into the posterior olfactory cortex (the olfactory tubercle and the piriform cortex), a target brain region of mitral cells, 5 weeks after the transection. FG (+) mitral cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In our previous study, we demonstrated that a functionally essential neuronal population exists for a specific neural function. 4,5,8,9,11,13,14,16 Similarly, concerning axonal components essential for normal motor function, approximately 40% of undamaged axons appear to be sufficient for normal motor function in rats with a common peroneal nerve-crush injury because the ratios of residual axons to acetylcholine receptors in the nervecrushed rats with normal motor function (SSI above -20) ranged from 36.5% to 88.7%, and the ratios for the success group in the slope-walking test at angles of 30° and 45° ranged from 14.7% to 88.7% and from 39.8% to 88.7%, respectively. However, for some nerve-injured rats, there were inconsistencies between motor function and the ratio of undamaged residual axons to acetylcholine receptors.…”
Section: Undamaged Residual Axons To Maintain Normal Motor Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we demonstrated that a functionally essential neuronal population exists for a specific neural function. 4,5,8,9,11,13,14,16 Similarly, concerning axonal components essential for normal motor function, approximately 40% of undamaged axons appear to be sufficient for normal motor function in rats with a common peroneal nerve-crush injury because the ratios of residual axons to acetylcholine receptors in the nervecrushed rats with normal motor function (SSI above -20) ranged from 36.5% to 88.7%, and the ratios for the success group in the slope-walking test at angles of 30° and 45° ranged from 14.7% to 88.7% and from 39.8% to 88.7%, respectively. However, for some nerve-injured rats, there were inconsistencies between motor function and the ratio of undamaged residual axons to acetylcholine receptors.…”
Section: Undamaged Residual Axons To Maintain Normal Motor Functionmentioning
confidence: 99%
“…4,5,8,9,11,13,14,16 However, the number of nerve fibers required at the neuromuscular junction to maintain normal motor function is unknown. Therefore, the purpose of this study was to evaluate the extent to which undamaged residual axons contributed to motor function, and to determine the minimum number of nerve fibers required to maintain normal motor function after nerve injury.…”
mentioning
confidence: 99%
“…We have recently reported regeneration of LOT in developing rats during the early suckling period [11,13], and such regeneration of LOT had critical periods early in life [13]. Interestingly, the regenerated olfactory system was functional 10 days [14] and 4…”
Section: Discussionmentioning
confidence: 96%
“…LOT transection was performed in P2 pups (n = 70) unilaterally on the left side, as described previously [11][12][13]. Briefly, the LOT was transected at the posterior half of the olfactory stria by inserting the tip of a knife (Ophthalmic Scleral MVR Knife, 25 gauge; Alcon, Tokyo, Japan) from the ventrolateral aspect of the head.…”
Section: Lot Transection and Retrograde Tracer Injectionmentioning
confidence: 99%
See 1 more Smart Citation